Przydatność i kierunki rozwoju dialektycznej koncepcji przedsiębiorczości organizacyjnej - Bratnicki, Mariusz; Gabryś, Bartłomiej J. (Usefulness and Directions of Corporate Entrepreneurship Framework Development: a Dialectical Approach, 2006)
In this paper we explore dialectical dynamics of corporate entrepreneurship in four arenas: strategic, political, administrative, and behavioral. After briefly reviewing the existing literature on corporate entrepreneurship, management and strategy theory, we propose a new theory of corporate entrepreneurship that is amenable to empirical testing and correction. The theory has two distinguished features. First, it focuses on the functions that organizational ideology and organizational learning serves for entrepreneurial processes. Second, it explicates the conditions under which the exploitation of dialectical dynamics of entrepreneurship in established organizations is and is not likely to facilitate the corporate entrepreneurship. Overall, we show that impact of corporate entrepreneurship directs directly and substantially on the degree to which the proper contradiction reconciliations are fulfilled competently at appropriate times in appropriate circumstances.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 25-31